1982
DOI: 10.1111/j.0954-6820.1982.tb01961.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure in Relation to the Renin—Angiotensin—Aldosterone System

Abstract: ABSTRACT. The relationship between blood pressure (BP) and the renin—angiotensin—aldosterone system was studied in a stratified random sample (n = 120) of 49‐year‐old men selected from a BP screening and covering a wide range of BPs. Only subjects not on antihypertensive treatment were included. None had malignant or secondary hypertension. Plasma renin activity, plasma concentrations of angiotensin II, aldosterone, sodium, potassium and noradrenaline and the 24‐hour urinary excretions of sodium, cortisol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Many studies [1][2][3][4][5] have indicated a positive association between aldosterone and hypertension; others [6][7][8] have shown that hypertensive patients had normal 6,8 or low 7 aldosterone levels compared with values in normotensive subjects. One of the reasons for these inconsistent results could be the confounding effect of antihypertensive medications, differences in time of blood sampling, body position and dietary sodium intake, which significantly affect aldosterone levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies [1][2][3][4][5] have indicated a positive association between aldosterone and hypertension; others [6][7][8] have shown that hypertensive patients had normal 6,8 or low 7 aldosterone levels compared with values in normotensive subjects. One of the reasons for these inconsistent results could be the confounding effect of antihypertensive medications, differences in time of blood sampling, body position and dietary sodium intake, which significantly affect aldosterone levels.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In most studies, longterm dietary sodium intake has not been considered. Most studies 1,[3][4][5][6][7][8] use spot urine samples, 1,7,8 24-h urine collection 4,6 and short-term dietary sodium restriction; 5,6 only one study 3 measured long-term habitual sodium intake using a dietary record. To evaluate the longterm effect of dietary sodium intake, we surveyed habitual dietary sodium intake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, aldosterone is also implicated in arterial and tissue remodelling and injury, especially under conditions of high salt intake, in addition to its classic effects on renal sodium reabsorption and potassium excretion [10]. Elevation in BP levels, as well as cardiovascular and renal damage, can occur as consequences of the integrated multiple functions of this highly regulated and complex system [11]. In fact, by acting with blockers of the RAAS, at appropriate doses and with various combinations, BP can be controlled from the very high values encountered in some circumstances, such as primary or secondary malignant hypertension up to the induction of orthostatic hypotension, severe dehydration and functional renal insufficiency.…”
Section: Introductionmentioning
confidence: 99%